Proactive coping and social-emotional adjustment among students with and without learning disabilities in Kerala, India - Deepthi, D. P.; Jeyavel, Sundaramoorthy; Subhasree, G.; Jojo, Chacko Eapen (Frontiers in Psychology, 2022)
The current study compared the level of proactive coping and social-emotional adjustment of students with and without learning disabilities. In addition to the relationship, influence of proactive coping on social-emotional adjustment of students with and without learning disabilities was also explored. Using a multistage random sampling method researcher selected students with and without learning disabilities in the age group of 15–17 years; each group consists of 150 participants from different high schools in Kerala. The instruments employed in this study were the Proactive Coping Inventory and the Adjustment Inventory for School Students-AISS. Correlation, t-test, and regression analysis were used to analyses the data. The students with learning disabilities have found to have lower levels of proactive coping and social emotional adjustment than those without learning disabilities. Further, a positive correlation between social emotional adjustment and proactive coping was also observed. The regression analysis has revealed that proactive coping of students with and without learning disabilities was significantly predicting their adjustment. As students with learning disabilities showing lower proactive coping skills, the study emphasizes the need to enhance proactive coping among students with learning disabilities. Improving proactive coping in both students with and without learning disabilities may help to mitigate social emotional adjustment issues.